Ethnomathematics in the Local Wisdom of Sasi Lompa in Haruku Village, Central Maluku: A Literature Study - Senny Idris; Djaffar Lessy; Patma Sopamena (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
Regency, which functions to preserve the sustainability of the coastal environment and prevent the overexploitation of lompa fish resources (Thryssa baelama). This literature study examines the practice of Sasi Lompa from an ethnomathematical perspective to reveal how mathematical concepts are integrated into cultural activities. The results of the analysis indicate that the Sasi procession reflects the application of arithmetic operations, such as counting the members of the kewang, the symbolic five beats of the tifa drum, the calculation of the closing and opening time cycles of Sasi, and the determination of the restricted area. The harvest- sharing mechanism also contains mathematical elements through proportional distribution, where 30% of the catch is allocated to vulnerable community groups. In addition, the implementation of customary sanctions in the form of symbolic punishments demonstrates the use of simple mathematical calculations within the social control system. From a geometric perspective, Sasi attributes such as woven young coconut leaves and the wooden Sasi marker represent plane geometric shapes (square, rectangle, rhombus, and semicircle) as well as three-dimensional shapes (the cylindrical form of the tifa drum). These findings confirm that ethnomathematics is contextually embedded in the Sasi Lompa tradition, which not only functions as a customary-based conservation instrument but also has the potential to be integrated into school mathematics learning. Therefore, this study contributes to the development of a local culture–based curriculum, strengthens cultural identity, and fosters ecological awareness among the younger generation